Analysis of The Influence of Motivation, Facilities and Location on Visiting Decisions (Case Study MH Museum. Good location" - Catur Widayati; Sri Vandayuli Riorini; Kornelia Johana Dacosta; Amirudin Wibowo (Social and Economic Bulletin, 2024)
MH Museum. Thamrin Jakarta was established in the 20th century as the Building of the Indonesian National Political Association (PPPKI). In the period 3 (three) years from 2013-2015 the number of visitors visited mh museum. Thamrin continues to experience significant declines. This is because visitors tend to be more interested in going to shopping centers or to more familiar tourist attractions. Therefore the authors conducted research on the Museum. This research aims to determine the influence of motivation, facilities and location on visiting decisions (case study at MH Museum. Thamrin Jakarta). The object of this research is visitors to mh museum. .11 miles away The study was conducted on 170 respondents using a quantitative descriptive approach. The data collection technique used is a questionnaire using purposive sampling. The data analysis used is SEM where data processing using SmartPLS 3.0.